2023
DOI: 10.1007/s11027-023-10046-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rewetting degraded peatlands on carbon fluxes: a meta-analysis

Abstract: Numerous studies claim that rewetting interventions reduce CO2 and increase CH4 fluxes. To verify the claim, we conducted a systematic review and meta-analysis of the effects of rewetting on CO2 and CH4 fluxes and dissolved organic carbon (DOC). We identified 28 primary articles eligible for meta-analysis, from which we calculated 48 effect sizes for CO2 emissions, 67 effect sizes for CH4 emissions, and 5 effect sizes for DOC. We found that rewetting significantly decreased CO2 fluxes, with temperate zones sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…Rewetting of drained organic soils is an effective measure to strongly reduce agricultural CO 2 emissions and to revert soil C sequestration in the short-term (Cabezas et al 2014 ; Nugent et al 2018 ). A recent meta-analysis by Darusman et al ( 2023 ) showed that rewetting reduced CO 2 emissions by 1.43 ± 0.35 Mg CO 2 -C ha −1 yr −1 on average, but the effects varied depending on climatic zone and nutrient status. Currently, CO 2 emission factors for rewetted peatlands are between − 0.34 and − 0.55 Mg CO 2 -C ha −1 yr −1 for boreal peatlands, − 0.23 and 0.5 Mg CO 2 -C ha −1 yr −1 for temperate peatlands, and 0 Mg CO 2 -C ha −1 yr −1 for tropical peatlands (Wilson et al 2016 ).…”
Section: Belowground Microbial Processes Involved In Ghg Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rewetting of drained organic soils is an effective measure to strongly reduce agricultural CO 2 emissions and to revert soil C sequestration in the short-term (Cabezas et al 2014 ; Nugent et al 2018 ). A recent meta-analysis by Darusman et al ( 2023 ) showed that rewetting reduced CO 2 emissions by 1.43 ± 0.35 Mg CO 2 -C ha −1 yr −1 on average, but the effects varied depending on climatic zone and nutrient status. Currently, CO 2 emission factors for rewetted peatlands are between − 0.34 and − 0.55 Mg CO 2 -C ha −1 yr −1 for boreal peatlands, − 0.23 and 0.5 Mg CO 2 -C ha −1 yr −1 for temperate peatlands, and 0 Mg CO 2 -C ha −1 yr −1 for tropical peatlands (Wilson et al 2016 ).…”
Section: Belowground Microbial Processes Involved In Ghg Dynamicsmentioning
confidence: 99%
“…High nutrient concentrations in peat soils, particularly in temperate peatlands, generate larger CO 2 emissions from rewetted sites (Wilson et al 2016 ; Hemes et al 2019 ; Tiemeyer et al 2020 ). Additionally, vegetation can affect emissions by adding fresh plant residues to the soil (Rigney et al 2018 ) or by transporting O 2 to the peat through roots (Zhong et al 2020 ; Darusman et al 2023 ) thereby increasing peat decomposition and CO 2 emissions. These emissions are governed by the dynamics between CO 2 uptake by ecosystems, i.e., photosynthesis by plants and soil autotrophic microorganisms (both photo- and chemoautotrophic), and loss to the atmosphere from ecosystem respiration (Fig.…”
Section: Belowground Microbial Processes Involved In Ghg Dynamicsmentioning
confidence: 99%
“…Peatland rewetting is performed in degraded and drained peatlands to restore hydrological conditions [29]. According to estimations, peatland rewetting is effective if the water table is 20-30 cm [29] below the peat surface throughout the year [29].…”
Section: Peatland Management and Restoration Strategiesmentioning
confidence: 99%
“…The water table is low at the drained peatland level; therefore, carbon dioxide (CO 2 ) emissions increase. In peatlands where drainage has been carried out, CO 2 is the main GHG emission [29]. It has been determined that drained peatland causes ~2% to 5% of the emissions of greenhouse gas (GHG) emissions and ~10% of CO 2 emissions in total [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation